Faktor-faktor yang mempengaruhi implementasi kebijakan pengembangan jaringan kantor PT. Bank Negara Indonesia(Persero)Tbk - Fachrisya Rachman; Martani Husaeni (Sekolah Pascasarjana Perbanas Jakarta, 2019)
This study aims to analyze the effectiveness implementation of branch network (outlet) development policies at PT. Bank Negara Indonesia (Persero) Tbk. The analysis techniques using the McKinsey 7'S model framework approach. The result shows that there are several factors that affecting strategy implementation these are strategy, organizational structure, system and procedure, skill and staff, leadership styles and organizational culture. Strategic implementation are formulated based on Corporate Plan, organizational structure is designed refers to the functions of organization, systems and procedures company has standarized and systematic, leadership style has a high commitment by providing direction, motivation and ability to adapt changing environment conditions and decision making processes involving subordinates and become a good role models, HR Planning and development refers to Human Capital Architecture, standardization capability in order to improve competencies of employees and internalization of corporate culture to achieve company vision. Based on the analysis in this study found some obstacles in strategy implementation : (1) lack of optimal outlet performance in achieving the target; (2) bureaucratic and weak coordination among units; (3) lack of compliance with company's system and procedures; (4) leadership style of top management; (5) resistance to performance appraisal system;(6) effectiveness training program and performance outcomes (7) consistency of corporate culture in units level. Key Words : Strategy Implementation, Model 7's McKinsey, Bank Network